Public sector efficiency: evidence for new EU member states and emerging markets - António Afonso; Ludger Schuknecht; Vito Tanzi (European Central Bank (ECB), 2006)
In this paper we analyse public sector efficiency in the new member states of the European Union compared to that in emerging markets. After a conceptual discussion of expenditure efficiency measurement issues, we compute efficiency scores and rankings by applying a range of measurement techniques. The study finds that expenditure efficiency across new EU member states is rather diverse especially as compared to the group of top performing emerging markets in Asia. Econometric analysis shows that higher income, civil service competence and education levels as well as the security of property rights seem to facilitate the prevention of inefficiencies in the public sector.
Keywords: C14; H40; H50; 330; DEA; Efficiency; emerging markets; Government expenditure; new EU member states; Öffentlicher Sektor; Effizienz; Data-Envelopment-Analyse; Vergleich; Schwellenländer; Asien; EU-Mitgliedschaft